Universal Basic Income – Empty Dreams of Paradise - Hilmar Schneider (Intereconomics, 2017)
The wealth of a society is created by allowing people to do what they do best. Achieving optimal resource allocation is one of the greatest challenges of every society. A UBI therefore offers the wrong incentives and tends to promote collective poverty, not only materially but also subjectively.
Keywords: 330